Hugo Chávez’ de-konstruktioner af det moderne Europa - Henriksen, Ken (K&K - Kultur og Klasse, 2009)
The Deconstruction of Modern Europe by Hugo Chávez: In recent years many countries in Latin America have undergone profound economic and political transformations, which among many other things have implied a »turn to the left«, a break with neoliberalism, and the upsurge of political viewpoints and discourses that are critical of North American influence in the area. But how is Europe represented in these anti-American discourses? This article is an investigation of Hugo Chávez’ discourse about Europe and European culture and politics. Taking its point of departure in the analysis of how Europe is portrayed in a political campaign which sought popular support for constitutional changes that would pave the way for indefinite re-election of the President, the article argues that Chávez seeks to demolish the image of a democratic and progressive Europe. Chávez’ discourse about Europe emphasizes internal, social problems and poverty in Europe, and he points at double standards of morality and the lack of capacity to solve Europe’s own problems. This means that he attempts to deconstruct the idea of Europe as a privileged centre of modernity, development and democracy. However, his discourse contributes simultaneously to the reproduction of binary distinctions between the »evil North« and the »wounded South«. Despite some important differences, Chávez’ portrayal of Europe therefore bears a resemblance to the negative ideas of the West that are often expressed in occidentalist discourses.